2019
DOI: 10.1016/j.dib.2019.104333
|View full text |Cite
|
Sign up to set email alerts
|

Data to model the effect of awareness on the success of IT Governance implementation: A partial least squares structural equation modeling approach (PLS-SEM)

Abstract: This article presents raw inferential statistical data that determine the influence of awareness on the successful implementation of IT Governance. Data were collected from respondents in all regions of Indonesia. Quantitative research methods are used to analyze data. The structured questionnaire was distributed to respondents in all regions of Indonesia who understood the field of IT Governance whose reliability and validity were confirmed. Structural equation modeling (SEM) using Smart PLS software, version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…It is because in practice, the two policies are implemented by all elements within the organization, not partial. This result is in line with Yudatama, Hidayanto, Nazief, and Phusavat (2019) that the awareness of organizational members is needed to achieve a successful IT governance JRAK 11.3 implementation within organization. In different context, a research by Dwianika, Murwaningsari, and Suparta (2020) also found the similar suggestion that water awareness has a significant role in improving the sustainability of firm's performance in urban areas in Indonesia.…”
Section: Discussionsupporting
confidence: 86%
“…It is because in practice, the two policies are implemented by all elements within the organization, not partial. This result is in line with Yudatama, Hidayanto, Nazief, and Phusavat (2019) that the awareness of organizational members is needed to achieve a successful IT governance JRAK 11.3 implementation within organization. In different context, a research by Dwianika, Murwaningsari, and Suparta (2020) also found the similar suggestion that water awareness has a significant role in improving the sustainability of firm's performance in urban areas in Indonesia.…”
Section: Discussionsupporting
confidence: 86%
“…SI GRC Implementation is still a novel paradigm [8], [11], [32]- [34]. Un iformity is still necessary from the standpoint of understanding [35]. Therefore, since understanding is not constantly consistent, applying SI GRC is only feasible to use a scientific approach [36].…”
Section: B Practical Implicationmentioning
confidence: 99%
“…SEM-PLS has been discussed widely and used in various fields, illustrate the econometric applications and interpretations of various PLS algoritms using R programming [3]; present a new approach to consumer behavior analysis by generating a tailor-made consumer behavior model [4]; introduce the essential components and variants of structural equation modeling (SEM), synthesize the common issues in SEM applications, and share our views on SEM's future in ecological research [5]; discussions, and developments have led to substantial changes in the understanding and use of PLS [6]; modeling health status by using structural equation modeling in Kediri Regency [7]; test islamic bank financing to small medium enterprises performance [8]; The Role of Perceived Control, Enjoyment, Cost, Sustainability and Trust on Intention to Use Smart Meters: An Empirical Study Using SEM-PLS [9]; model the effect of awareness on the success of IT Governance implementation: A partial least squares structural equation modeling approach [10]; test the mediating effect of overall fairness between specific justice type and employees' citizenship behaviour and psychological ownership [11]; identify paths and predictive power of students' satisfaction during team-based learning (TBL) activities in the faculty of life sciences using partial least squares structural equation modelling [12]; explains how to perform and report empirical analyses using PLS-PM including the latest enhancements, and illustrates its application with a fictive example on business value of social media [13].…”
Section: Introductionmentioning
confidence: 99%